x-3x+5=3x-1

Simple and best practice solution for x-3x+5=3x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-3x+5=3x-1 equation:


Simplifying
x + -3x + 5 = 3x + -1

Reorder the terms:
5 + x + -3x = 3x + -1

Combine like terms: x + -3x = -2x
5 + -2x = 3x + -1

Reorder the terms:
5 + -2x = -1 + 3x

Solving
5 + -2x = -1 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
5 + -2x + -3x = -1 + 3x + -3x

Combine like terms: -2x + -3x = -5x
5 + -5x = -1 + 3x + -3x

Combine like terms: 3x + -3x = 0
5 + -5x = -1 + 0
5 + -5x = -1

Add '-5' to each side of the equation.
5 + -5 + -5x = -1 + -5

Combine like terms: 5 + -5 = 0
0 + -5x = -1 + -5
-5x = -1 + -5

Combine like terms: -1 + -5 = -6
-5x = -6

Divide each side by '-5'.
x = 1.2

Simplifying
x = 1.2

See similar equations:

| 5m(2m^2-n^3)= | | (5n-18)+(2n+12)=180 | | 3+5x=x+15 | | (4x-1)(x-9)=0 | | -3(m+4)=4 | | y=(7x+9)(x-1) | | 105=-3x+5(-3x+3) | | 7m-3m+4=16 | | 5lnx=30 | | 18y=12-12x | | =2500-2x | | 7x-6=3(x^6) | | (12x+10)-(-4x-6x+10)= | | 6[-6x+6+4x(x+1)]=6x+2 | | 0.5x+0.25=x | | 3x+3(5x-10)=138 | | (2mn+8m^2n-5n+6m)= | | 0=(t-20)+(t-400) | | 8.57x+17.14=34.28 | | t-20=t-400 | | (2mn+8m^2n-5n+6m)(10mn^2)= | | 3cos(x)=8-4sec(x) | | Y=2500-2x | | 10x+4x+4+9=4x+3+9x | | x^2+4x=47 | | 3.91x+16=15.2881+4x | | 3cosx=8-4secx | | v^2=18v | | -5(4b+4)+(21b-7)=0 | | R^2-4r-6=0 | | (x^2-10x)+(y^2-6y)=-33 | | y(-2)=-6.8(-2)+5 |

Equations solver categories